2016
DOI: 10.3389/fneur.2016.00187
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Secondary Hematoma Expansion in Spontaneous Intracerebral Hemorrhage – State of the Art

Abstract: Spontaneous intracerebral hemorrhage (SICH), defined broadly as intracerebral hemorrhage not related to trauma, results in long-term disability or death in a large proportion of afflicted patients. Current management of this disease is predominantly supportive, including airway protection, optimization of hemodynamic parameters, and management of intracranial pressure. No active treatments that demonstrate beneficial effects on clinical outcome are currently available. Animal models of SICH have allowed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 80 publications
0
7
0
3
Order By: Relevance
“…Recently, several therapeutic targets were identified and candidate drugs were evaluated in clinical trials34. Unfortunately, however, there is still no effective treatment which increases survival or improves the quality of life after ICH5. Early surgery may limit the toxic effects of blood clot, but many clinical trials of clot evacuation in ICH have not shown a definitive benefit for surgical removal, which might reflect some of the adverse side effects of surgery267.…”
mentioning
confidence: 99%
“…Recently, several therapeutic targets were identified and candidate drugs were evaluated in clinical trials34. Unfortunately, however, there is still no effective treatment which increases survival or improves the quality of life after ICH5. Early surgery may limit the toxic effects of blood clot, but many clinical trials of clot evacuation in ICH have not shown a definitive benefit for surgical removal, which might reflect some of the adverse side effects of surgery267.…”
mentioning
confidence: 99%
“…About 30% of patients with sICH have hematoma expansion (HE), and HE is associated with a poor outcome in terms of neurological function (3). Some predictors associated with HE have been identified in neuroimaging data from patients with sICH, and these predictors can help to identify patients at risk of HE and to improve clinical outcomes (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…ВМК могут развиваться спонтанно на фоне интактного гемостаза (гипертония, амилоидная ангиопатия у пожилых, применение кокаина и др.) или его нарушений (врожденные или лекарственно индуцированные коагулопатии) [52,54,56,[58][59][60]72]. Продолжительные нейрохирургические вмешательства, направленные на устранение последствий ВМК, по данным различных кооперативных исследований (например, STICH [57]), имеют достаточно узкие показания.…”
unclassified
“…Продолжительные нейрохирургические вмешательства, направленные на устранение последствий ВМК, по данным различных кооперативных исследований (например, STICH [57]), имеют достаточно узкие показания. В настоящее время в лечении таких пациентов применяются главным образом консервативная терапия либо малоинвазивные нейрохирургические вмешательства [52,54,55,58,59,[61][62][63]. Один из основных факторов прогрессирующего ухудшения состояния у таких пациентов -вторичное увеличение объема ВМК, что отмечается, как минимум, у 30% пациентов [52,58,59,68,69].…”
unclassified
See 1 more Smart Citation